2009
DOI: 10.1080/13518470903345729
|View full text |Cite
|
Sign up to set email alerts
|

The informational impact of electronic trading systems on the FTSE 100 stock index and its futures contracts

Abstract: This article examines the partial adjustment factors of Financial Times Stock Exchange (FTSE) 100 stock index and stock index futures. Using high frequency data from 15 January 1997 to 17 March 2000, it aims to assess the informational impact of the electronic trading systems implemented at the London Stock Exchange and London International Financial Futures Exchange (LIFFE). The results suggest that information runs mainly from the futures market to the spot market. We find that the introduction of stock exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Amongst the wide range of outputs in this regard are studies of algorithmic trading patterns (Prix et al, 2007), liquidity determination (Daníelsson and Payne, 2012), liquidity premium (Rubio and Tapia, 1998) and other factors relating to price discovery (Dunne et al, 2011;Sebastião, 2010) as well as analyses based on Monte Carlo simulation.…”
Section: Cluster #4: Stock Markets (Represented In Black)mentioning
confidence: 99%
“…Amongst the wide range of outputs in this regard are studies of algorithmic trading patterns (Prix et al, 2007), liquidity determination (Daníelsson and Payne, 2012), liquidity premium (Rubio and Tapia, 1998) and other factors relating to price discovery (Dunne et al, 2011;Sebastião, 2010) as well as analyses based on Monte Carlo simulation.…”
Section: Cluster #4: Stock Markets (Represented In Black)mentioning
confidence: 99%
“…In contrast, various studies have shown that derivative markets lead the cash markets, providing greater price discovery (see, e.g., Garbade & Silber, 1983 for an early reference). This recently has also been shown to be the case for the FTSE 100 index futures contracts (see Sebastião, 2010).…”
mentioning
confidence: 62%
“…The change from floor‐based trading to electronic trading has profound impacts on the market microstructure of the futures contracts as documented by Aitken, Frino, Hill, and Jarnecic (), Gilbert and Rijken (), Ning and Tse (), Sebastião (), and ap Gwilym and Meng ().…”
mentioning
confidence: 99%